HUBUNGAN PENGETAHUAN DENGAN KESIAPSIAGAAN MASYARAKAT TERHADAP BENCANA BANJIR DI DESA BETALEMBA KABUPATEN POSO - Ulfa Sufyaningsi; Najamuddin, Nur Isriani; Hestiani K, Dewi; Rantesigi, Nirva (Bina Generasi : Jurnal Kesehatan, 2024)
Background: Flooding is one of the natural disasters occurring in many cities worldwide and has significant impacts on physical and psychological health, as well as property damage and loss. Community preparedness in facing flood disasters is essential to mitigate these impacts. Objective: To examine the relationship between knowledge and community preparedness attitudes toward flood disasters in Betalemba Village, Poso Regency. Research Method: This study employs a quantitative research design with a cross-sectional approach. Purposive sampling was used to recruit 91 community members from Betalemba Village in Poso Regency, Central Sulawesi Province, Indonesia. Data were collected using the Community Knowledge of Flood Disasters Questionnaire and the Community Preparedness Attitudes Toward Flood Disasters Questionnaire. Fisher’s Exact test was used to examine the relationship between variables. Results: There is a significant relationship between community knowledge and community preparedness attitudes toward flood disasters (p = 0.023 < 0.05). Conclusion: Knowledge is related to community preparedness attitudes toward flood disasters in Betalemba Village, Poso Regency. Suggestion: This study recommends implementing activities to enhance community preparedness attitudes in facing flood disasters, such as introducing flood disaster knowledge and participating in disaster preparedness training.